Possible Emergence of West Caucasian Bat Virus in Africa - Kuzmin, Ivan V.; Niezgoda, Michael; Franka, Richard; Agwanda, Bernard; Markotter, Wanda; Beagley, Janet C.; Urazova, Olga Yu; Breiman, Robert F.; Rupprecht, Charles E. (Emerging infectious diseases, 2008)
The prevalence of neutralizing antibody against West Caucasian bat virus (WCBV) in Miniopterus bats collected in Kenya ranged from 17% to 26%. Seropositive bats were detected in 4 of 5 locations sampled across the country. These findings provide evidence that WCBV, originally isolated in Europe, may emerge in other continents.